Optimization of cable connection layout of unattended AC/DC joint construction station based on INFO algorithm - Hu, Long; Yu, Zhiwei; Liang, Minxin; Chen, Xiaoying; Chen, Lixia; Huang, Guohui (Discover applied sciences, 2025)
In order to improve the comprehensive evaluation performance of the optimization of cable connection layout for unattended AC and DC joint construction stations, and avoid falling into local optimal solutions in the optimization process. An optimization method based on INFO algorithm for cable connection layout of unattended AC-DC joint construction station is studied. The cable topology of the unattended AC/DC combination station is built according to the cable connection principle of an unattended AC/DC combination station. The INFO method is an effective means for optimizing the cable connection layout of unmanned AC/DC co construction stations. It is a population-based optimization algorithm that performs search optimization by calculating the weighted average of vectors. Based on the cable connection principle of the unattended AC/DC common station, the cable topology is constructed, and the optimization model is established with the objective function of minimizing the total cost of laying cables, and the constraints that the cable laying capacity is smaller than the channel capacity. Using the INFO algorithm, the feasible solutions of the model are formed into a search domain and solved, and finally the optimal cable connection layout results are output. The experimental results show that the channel capacity occupancy rate is significantly reduced, and the cable material reduction is more than 10% by using this method to optimize the cable connection layout of the unattended AC/DC composite station. It effectively improves the comprehensive evaluation performance of the cable connection layout and provides strong support for the stable operation of the power system and the construction of smart grid. Article Highlights Decrease cable—laying costs by reducing cable usage Reduce the channel capacity occupancy rate Enhance the power system's stability